2016
DOI: 10.1038/srep31796
|View full text |Cite
|
Sign up to set email alerts
|

Chiral light intrinsically couples to extrinsic/pseudo-chiral metasurfaces made of tilted gold nanowires

Abstract: Extrinsic or pseudo-chiral (meta)surfaces have an achiral structure, yet they can give rise to circular dichroism when the experiment itself becomes chiral. Although these surfaces are known to yield differences in reflected and transmitted circularly polarized light, the exact mechanism of the interaction has never been directly demonstrated. Here we present a comprehensive linear and nonlinear optical investigation of a metasurface composed of tilted gold nanowires. In the linear regime, we directly demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
42
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 24 publications
(35 reference statements)
1
42
0
Order By: Relevance
“…Both P-and S-polarization components of the SHG intensities are recorded for left and right CPL incident on the sample. The normalized SHG-CD is calculated as [9,18,42] where ω is the frequency of light and I…”
Section: Doi: 101002/adma201605110mentioning
confidence: 99%
See 1 more Smart Citation
“…Both P-and S-polarization components of the SHG intensities are recorded for left and right CPL incident on the sample. The normalized SHG-CD is calculated as [9,18,42] where ω is the frequency of light and I…”
Section: Doi: 101002/adma201605110mentioning
confidence: 99%
“…An example of an undesirable complication is extrinsic chirality, [15,16] which affects the nonlinear susceptibility tensor components in SHG. [17,18] Any anisotropy present in the sample can have a similar effect and our work here focuses on highlighting the effects of rotational anisotropy. We begin by selecting the sample geometry.…”
mentioning
confidence: 99%
“…The light that impinges on such structures under a proper oblique angle will be differently absorbed for circular polarizations of opposite handedness; this optical activity is usually indirectly measured as a difference in power transmitted/reflected by the chiral nanostructure-setup. More recently, we have shown that photoacoustic technique can be applied to directly measure circular dichroism in arrays of tilted gold NWs [23] as well as size-dependent resonant absorption properties of semiconductor NWs. [33] Here, we apply the same technique to investigate the "extrinsic" chirality in GaAs-based metal-semiconductor hybrid NWs under two wavelengths, 532 and 980 nm, corresponding to optical region of different light absorption by GaAs.…”
Section: Introductionmentioning
confidence: 99%
“…[20] This is called "extrinsic" chirality; in our previous works we have investigated this type of chirality in tilted golden nanowires by means of both linear (reflection and absorption) and nonlinear (second harmonic generation) measurements. [20][21][22][23] III-V semiconductor nanowires (NWs) have been widely investigated since they exhibit good waveguiding properties thus offering a light manipulation at nanoscale. Coupling of the incident light to the discrete leaky waveguide modes above the bandgap in NWs leads to increased resonant absorption, thus paving the way for important applications such as energy harvesting, spectral selectivity, lasing, spin angular momentum generation, etc.…”
mentioning
confidence: 99%
“…[19][20][21] Moreover, it was recently applied to study semiconductor nanowires, 22 and their resonant absorption, 23 as well as chirality when nanowires are partially covered with gold. 24,25 However, to our knowledge little work has been done on the detection of propagating surface plasmon polaritons by means of PA technique. Our PA and optical transmission set-up is shown in Fig.…”
Section: © 2017 Author(s) All Article Content Except Where Otherwismentioning
confidence: 99%